Modeling the effect of information campaigns on the HIV epidemic in Uganda - Hem Joshi; Suzanne Lenhart; Kendra Albright; Kevin Gipson (Mathematical Biosciences and Engineering)
The increasing prevalence of HIV/AIDS in Africa over the past twenty-five years continues to erode the continent's health care and overall welfare. There have beenvarious responses to the pandemic, led by Uganda, which has had the greatestsuccess in combating the disease. Part of Uganda's success has been attributed toa formalized information, education, and communication (IEC) strategy, loweringestimated HIV/AIDS infection rates from 18.5% in 1995 to 4.1% in 2003. Weformulate a model to investigate the effects of information and education campaignson the HIV epidemic in Uganda. These campaigns affect people's behavior andcan divide the susceptibles class into subclasses with different infectivity rates.Our model is a system of ordinary differential equations and we use data about theepidemics and the number of organizations involved in the campaigns to estimatethe model parameters. We compare our model with three types of susceptibles toa standard SIR model.